LITERATUR REVIEW: FAKTOR-FAKTOR YANG MEMPENGARUHI ANGKA KEKAMBUHAN PASIEN GANGGUAN JIWA (SKIZOFRENIA) - Rahajeng Win Martani; Moh. Projo Angkasa; Dewi Puji Astuti (LPPM Universitas Pekalongan, 2022)
WHO states that schizophrenia reach the second highest rank after infectious diseases. 45% population of mental hospitals in the world are schizophrenic patients who stay for a long time due to repeated relapses. Relapse will lead to negative effect such as tantrums, act anarchically, or even hurt others or suicide. Negative effect will lead public assumption that skizoprenia can’t be cured, eventhough individual factors such as emotional expression, family support, medication adherence factors and the social environment were also take a role caused relapse. This study aims to determine the factors that influence the relapse rate of schizophrenic patients, so that it can be used as a reference for developing strategies to overcome recurrent relapses in schizophrenic patients. The results show that the majority factors caused relapse were family support, medication adherence, and social support. The result of this study indicate the importance of the role of the family, patients compliance in taking medication, and support from the surrounding environment in the treatment of paranoid schizophrenic patients.